2019
DOI: 10.1002/wnan.1589
|View full text |Cite
|
Sign up to set email alerts
|

The role of sex in particle‐induced inflammation and injury

Abstract: The use of engineered nanomaterials within various applications such as medicine, electronics, and cosmetics has been steadily increasing; therefore, the rate of occupational and environmental exposures has also increased. Inhalation is an important route of exposure to nanomaterials and has been shown to cause various respiratory diseases in animal models. Human lung disease frequently presents with a sex/gender‐bias in prevalence or severity, but investigation of potential sex‐differences in the adverse heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 145 publications
(193 reference statements)
0
6
0
Order By: Relevance
“…Males and females have different air absorption capabilities, and the permeability of the gas-blood barrier differs by sex 52 . The inflammatory response is another important mechanism that is considered as an intermediate step in the link between air pollution and health 53 . Sexual differences in antioxidant status may have different effects on inflammatory and oxidative stress processes in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Males and females have different air absorption capabilities, and the permeability of the gas-blood barrier differs by sex 52 . The inflammatory response is another important mechanism that is considered as an intermediate step in the link between air pollution and health 53 . Sexual differences in antioxidant status may have different effects on inflammatory and oxidative stress processes in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Although very few reports exist, in vivo studies have shown the gender-dependent toxicity of AgNPs in the lungs could be related to hormone signaling, lung physiology, and respiratory immune function [93]. Ovarian hormones are usually associated with a proinflammatory response in the lungs [94], such as airway inflammation in asthma [95].…”
Section: Gendermentioning
confidence: 99%
“…One critically understudied aspect of nanotoxicology is sex as a biological variable, yet sex and/or gender‐based outcomes have long been established in respiratory disease 10,11 . However, delineating between sex and gender requires careful consideration and nuanced analysis in human research 12,13 ; therefore, our current knowledge base is largely dependent upon mechanisms identified using animal models.…”
Section: Introductionmentioning
confidence: 99%